Variation in time of day of anthesis in rice in different climatic environments - Julia C; Dingkuhn, Michael (Elsevier, 2012)
Thermal stress and in particular heat during anthesis causes sterility in rice inflorescences. Rice spikelets open in the morning and close a few hours later. Genotypic variation in the time of day of anthesis is considered an escape mechanism from thermal stress, but little is known on its dependency on environmental conditions. One traditional, cold-tolerant rice cultivar and three improved tropical rice cultivars were grown in four different climatic environments under flooded conditions to study the environmental response of time of day of anthesis. The environments were the cold-dry season and the hot-dry season in Senegal, the temperate summer in Southern France and the dry season in the Philippines. The time of day when the first spikelets opened, a maximum of spikelets were open and the last spikelets closed was observed daily on a population basis (2 m2 plots replicated 3 times). The time of these observations was expressed as hours after sunrise (hasr) calculated from astronomic day length and the local time of solar noon. Aggregate flowering periods were 4 10 d at panicle scale and 14 32 d at population scale. Within a day, onset of anthesis was earliest in the Philippines (3.4 hasr) and latest in the cool season in Senegal (6.75 hasr), the other environments being intermediate. The duration from onset to end of anthesis varied between 1.82 h in the Philippines and 2.77 h in France. Genotypic differences in time of anthesis and duration of anthesis were small. Across all genotypes and environments, 80% of the variation of the time of maximum anthesis could be explained with the mean minimum air temperature (Tmin) during the 7 d preceding any given anthesis event. Linear, multiple regression models determined for each cultivar using Tmin and vapor pressure deficit (VPD) observations from the three tropical environments explained 94% of variation of time of anthesis onset and end. Low Tmin thereby delayed and low VPD advanced anthesis processes. Under the assumption that panicle temperature during anthesis is indeed a major determinant of spikelet fertility in rice, it is concluded that the sensitivity of time of day of anthesis to air temperature and humidity is an effective eco-physiological adaptation of the rice crop. Prospects for improved modeling approaches for the prediction of thermal sterility in rice are discussed.